Economics : an A-Z guide / (Acc. D2118) - Bishop, Matthew (London : The Economist Books, 2016)
Everything you need to know about economics in a strikingly attractive paperback format with flaps. Following an introduction entitled the "Joy of Economics", which explains what economics is about, its strengths and shortcomings and the challenges facing economists today, the bulk of the book is an expansive A-Z with several hundred entries that explain with the essentials of economics - as well as some of its more arcane aspects. Entries include: Absolute advantage, Adverse selection, Animal spirits, Asymmetric shock, Backwardation, Bounded rationality, Capital flight, Deflation, Development economics, Diminishing returns, Elasticity, Endogenous, Exogenous, Free rising, Giffen goods, Gini coefficient, Hysteresis, Invisible hand, Liquidity trap, Macroeconomics, Microeconomics, Opportunity cost, Pareto efficiency, Queuing, Random walk, Say's law, Transaction costs, Utility, Velocity of circulation, Weightless economy, Yield Gap and Zero sum game.